2020
DOI: 10.1038/s41398-020-01000-3
|View full text |Cite
|
Sign up to set email alerts
|

The type of stress matters: repeated injection and permanent social isolation stress in male mice have a differential effect on anxiety- and depressive-like behaviours, and associated biological alterations

Abstract: Chronic stress can alter the immune system, adult hippocampal neurogenesis and induce anxiety- and depressive-like behaviour in rodents. However, previous studies have not discriminated between the effect(s) of different types of stress on these behavioural and biological outcomes. We investigated the effect(s) of repeated injection vs. permanent social isolation on behaviour, stress responsivity, immune system functioning and hippocampal neurogenesis, in young adult male mice, and found that the type of stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 129 publications
(135 reference statements)
5
36
0
Order By: Relevance
“…However, the models reviewed here mostly lack psychosocial stressors and thus are much more CPPS than CPSS models [ 25 , 154 ]. In this regard and in line with existing research [ 155 157 ], Du Preez et al [ 158 ] previously showed distinct behavioural and neurobiological differences between CPSS, CPPS and combined CPSS/CPPS paradigms in male mice. Repeated saline injections led to anxiety-like behaviour in the OFT and NSFT, increased M/Ms activation and reduced TNF-α serum levels, corticosterone reactivity and hippocampal neuroplasticity.…”
Section: Discussion and Perspectivessupporting
confidence: 84%
“…However, the models reviewed here mostly lack psychosocial stressors and thus are much more CPPS than CPSS models [ 25 , 154 ]. In this regard and in line with existing research [ 155 157 ], Du Preez et al [ 158 ] previously showed distinct behavioural and neurobiological differences between CPSS, CPPS and combined CPSS/CPPS paradigms in male mice. Repeated saline injections led to anxiety-like behaviour in the OFT and NSFT, increased M/Ms activation and reduced TNF-α serum levels, corticosterone reactivity and hippocampal neuroplasticity.…”
Section: Discussion and Perspectivessupporting
confidence: 84%
“…Other groups demonstrated that psychological stress using a communication box increased acutely blood corticosterone levels but did not change after 15 or 30 days-stress exposure [45,50]. Repeated injection stress for 6 weeks increased corticosterone reactivity, while the social isolation decreased the corticosterone reactivity [51]. We assumed that corticosterone is more reactive to physical stress than psychological stress and we observed the significant reduction of corticosterone levels in physical, not psychological stress.…”
Section: Discussionsupporting
confidence: 48%
“…Rats growing in post-weaning social isolation (SI-reared) develop an "isolation-induced stress syndrome" with excessive reactivity to handling, anxiety-like behavior and high emotionality [75,235]. Male and female SI-reared rats demonstrate good face validity of the depressive-like phenotype with increased motor locomotion [75][76][77] and decreased time spent in the arena center [78] in the open field test, and increased anxiety-like behaviors tested by the elevated plus maze [79][80][81]. These effects are irreversible by resocialization [236], as observed in males but not in females [237,238].…”
Section: Post-weaning Social Isolation Stressmentioning
confidence: 99%